Analisis Pengembangan Digitalisasi Koperasi Dalam Upaya Meningkatkan Partisipasi Anggota - Dadan Hamdani (Coopetition : Jurnal Ilmiah Manajemen, 2023)
The Indonesian Tempe and Tofu Producers Cooperative is a primary cooperative belonging to the type of producer cooperative and has 3 units, namely: a savings and loan unit, a soybean trading unit, and a non-soybean trading unit. This study aims to determine the development of cooperative digitalization to increase member participation. The method used in this research is a case study method by describing each related variable through data collection with questionnaires and literature study. Members of The Indonesian Tempe and Tofu Producers Cooperative responded positively to digitization and welcomed the digitization policy by participating in every activity carried out by the cooperative and always following the information that was spread. This policy is a distinct advantage for cooperatives because if it is realized, the opportunities for cooperatives to compete with other business entities and expand their reach will be more wide open. That way, cooperative efforts to increase member participation will be more real to be realized.